LexVet-Esp: developing a new vocabulary test and the integration of VR for specialized vocabulary acquisition - Izquierdo García, Paula, author; Miller de Rutté, Alyssia, advisor; Zeller, Shannon, committee member; Edwards-Callaway, Lily, committee member (Colorado State University. Libraries, 2025)
The number of Spanish speakers in the U.S. continues to increase, which leads to a growing population of individuals who do not speak English as their primary language, making access to various services, including veterinary care, difficult. To address this issue, Languages for Specific Purposes (LSP) courses have been developed to train (future) professionals to speak in their client's preferred language. Alongside the rising popularity of LSP courses, technological advancements have also been implemented in language education. Virtual reality (VR) platforms and artificial intelligence (AI) are two examples of relevant tools in second language learning as they allow for the integration of immersive and interactive experiences. This thesis aimed to combine LSP, particularly in Spanish for Veterinary Medicine, and technology to understand the potential effects on language learners' vocabulary acquisition and retention. The thesis was divided into two projects. The first project focused on developing an assessment tool to test learners' receptive vocabulary knowledge, defined as words that learners can recognize even if they cannot yet define or use them in different contexts. This assessment builds upon previous studies, which created validated and reliable instruments for measuring vocabulary and proficiency levels. A specialized vocabulary test for Veterinarian Spanish (known as the LexVet-Esp) was developed and validated. The second project implemented a VR/AI platform as part of a Spanish for Veterinary Medicine course and used the LexVet-Esp to assess the impact of the technology on vocabulary acquisition and retention and whether explicit or implicit vocabulary exercises contributed to language development. To examine this, students completed the vocabulary test four times. The first test, administered during week nine of a sixteen-week semester, served as the pre-test as participants had not yet interacted with the VR/AI platform. Students took the test again in week twelve after completing three weeks of explicit vocabulary exercises on the platform and again in week fifteen after completing implicit vocabulary activities. Finally, a fourth test was conducted three months after the end of the course to determine long-term vocabulary retention. The results did not show significant differences across the tests, which may have been influenced by the short length of the study (six weeks) and the small sample size (n=15). Despite the lack of statistically significant differences across the tests, results indicated varying complexities related to the vocabulary acquisition and retention processes. Pedagogical implications and future research opportunities are discussed.